2011
DOI: 10.1111/j.1442-2042.2011.02850.x
|View full text |Cite
|
Sign up to set email alerts
|

Naftopidil vs silodosin in medical expulsive therapy for ureteral stones: A randomized controlled study in Japanese male patients

Abstract: Abstract:The aim of the present study was to compare the efficacy of the selective a1D-adrenoceptor antagonist naftopidil and the selective a1A-adrenoceptor antagonist silodosin (as an example) in the management of ureteral stones in Japanese male patients. A total of 74 patients with symptomatic Յ10 mm ureteral stones were enrolled in a prospective study and randomized into two groups: Group 1 received 50 mg naftopidil daily, whereas Group 2 received 8 mg silodosin daily. Patients were followed-up for up to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
(35 reference statements)
2
33
1
1
Order By: Relevance
“…Tatemichi et al [10] reported that in hamster ureter, ureteral contraction was mediated mainly by alpha-1A adrenoreceptor even though alpha-1D receptor are more prevalent so we used silodosin which is highly selective alpha-1A adrenoceptor antagonist and has 56 fold affinity for alpha-1A over alpha-1D adrenoceptor. [11,12] Gratzke et al [13] demonstrated the effectiveness of PDE 5 inhibitors vardenafil, sildenafil, and tadalafil in relaxation of ureteral smooth muscle in order of decreasing potency. [14,15] As tadalafil is more selective PDE-5i receptor as compared to sildenafil, visual problems are less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Tatemichi et al [10] reported that in hamster ureter, ureteral contraction was mediated mainly by alpha-1A adrenoreceptor even though alpha-1D receptor are more prevalent so we used silodosin which is highly selective alpha-1A adrenoceptor antagonist and has 56 fold affinity for alpha-1A over alpha-1D adrenoceptor. [11,12] Gratzke et al [13] demonstrated the effectiveness of PDE 5 inhibitors vardenafil, sildenafil, and tadalafil in relaxation of ureteral smooth muscle in order of decreasing potency. [14,15] As tadalafil is more selective PDE-5i receptor as compared to sildenafil, visual problems are less likely.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Tamsulosin, doxazosin, alfuzosin, silodosin, nifedipine and naftopidil are the most commonly used drugs in MET. 8,10,12 In this study, we compared the efficacy of tamsulosin and nifedipine in MET for distal ureteral stones in patients with renal colic. In addition, during these treatment modalities, we evaluated the value of Hounsfield Unit (HU) of the stone detected in a non-contrast computerized tomography (NCCT) in the prediction of MET success rate.…”
Section: Introductionmentioning
confidence: 99%
“…(15) Tsuzaka compared the efficacy of the selective α1D AR antagonist naftopidil and the selective α1A AR antagonist silodosin in the management of symptomatic ≤10 mm ureteral stones. (16) Vittorio Imperatore et al, compared for the first time tamsulosin and silodosin in the context of MET for distal ureteric stones. (17) In patients presenting with DUS of 610 mm without the use of MET, the reported spontaneous stone clearance rates are between 35.2% and 61% with mean expulsion times ranging between 9.87 and 24.5 days.…”
Section: Discussionmentioning
confidence: 99%